Overweight and abdominal obesity in adults living with HIV/AIDS - Castro,Aline de Cássia Oliveira (2016)
Summary Objective: To investigate the prevalence of overweight, abdominal obesity and associated factors in people living with HIV/AIDS (PLWHA). Method: Cross-sectional study with 270 PLWHA. A questionnaire was applied to investigate sociodemographic, clinical and lifestyle characteristics. Weight, height and waist circumference were measured. BMI ≥25 kg/m2 was considered overweight, while abdominal obesity referred to waist circumference ≥102 cm for men and ≥88 cm for women. The authors used multiple Poisson regression with 5% significance level. Results: The prevalence of overweight and abdominal obesity was 33.7% and 12.6%, respectively, referring to 37.9% of women and 5.7% of men (p<0.001). Overweight was associated with age of 40-49 years and ≥50 years, non-use of ARV therapy, and lower tertile of consumption of risk foods. Abdominal obesity was associated with: female gender, age of 40-49 years and ≥50 years, income greater than four times the minimum wage, and CD4+ lymphocyte count >350 cells/mm3. Conclusion: There was a high prevalence of overweight and abdominal obesity associated with sociodemographic and clinical conditions, and consumption of risk foods. This scenario indicates the need for reorientation of the health care focus in this population.